Bitcoin - Between Legal and Informal - Loredana Maftei (CES Working Papers, 2014)
The proliferation of technology emphasized new forms of payment. During the last years, current literature highlighted the role of virtual currency, the channels of payment through digital coins and the importance of assimilation of such platforms. Bitcoin or BTC is known as a digital coin, issued for the first time in 2009 and based on a peer to peer system. The difference from other forms of payment is that BTC is not controlled by any institution or central authority. BTC transactions have grown rapidly, ”asking" for regulation measures or legal approval of governments. Although BTC has become very popular, the market is poor and unfortunately of no confidence. There is a lack of regulation which can determine a number of risks associated with criminal financing activities. However, the legal status of Bitcoin is present in many European countries like Belgium, Bulgaria, Denmark, Finland, Germany, Lithuania, Norway, Poland, Slovenia, Switzerland or Turkey. Also, this type of currency has experienced a rapid evolution among coffee shops and restaurants.
Keywords: E44; F62; H27; 330; virtual currency; intelligence technology; Bitcoin; globalization